2019
DOI: 10.4103/jos.jos_97_18
|View full text |Cite
|
Sign up to set email alerts
|

Do facial morphology, posture and function change following glossectomy? A systematic review

Abstract: OBJECTIVES: To systematically investigate and critically appraise the quality of the currently available literature regarding the morphological, postural, and functional changes observed in individuals following glossectomy. MATERIALS AND METHODS: A search without restrictions in eight databases (including grey literature) and hand searching from inception until March 2018 was performed. Data on morphological, postural, and functional changes after glossectomy were revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
(47 reference statements)
0
0
0
Order By: Relevance
“…A recently published systematic review on the subject found no significant differences in the medium term regarding the adaptation of dentofacial structures and language function after glossectomy. 10 Still, supporting speech therapy is essential after orthognathic surgery and glossectomy. 11 It aims to help reestablish normal tongue mobility and word articulation, ef- fectively improving speech intelligibility in the postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published systematic review on the subject found no significant differences in the medium term regarding the adaptation of dentofacial structures and language function after glossectomy. 10 Still, supporting speech therapy is essential after orthognathic surgery and glossectomy. 11 It aims to help reestablish normal tongue mobility and word articulation, ef- fectively improving speech intelligibility in the postoperative period.…”
Section: Discussionmentioning
confidence: 99%